2023
DOI: 10.1037/ser0000642
|View full text |Cite
|
Sign up to set email alerts
|

Reset for systematic action: Removing VA barriers to housing and treatment for military veterans with sexual offenses.

Abstract: Though the U.S. Department of Veterans Affairs (VA) provides housing, residential treatment, and mental health care to justice involved veterans, those with sexual offenses face daunting obstacles to securing such services, including exclusion from housing programs, and lack of mental health services to treat sexual deviancy disorders. The VA's strategy to date may reflect a large system's caution in systematically addressing a problem that involves a population with an even higher degree of stigma than homele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…A study in the UK identified 5 common themes (employment, housing, skills and experience, physical/psychological wellbeing, and addictions/antisocial behavior) in which stigmatization was made based on erroneous stereotypes that exacerbated the difficulties toward social reintegration (Phillips, 2020). Intersectionality aspects may also be considered in the case of homeless veterans who are also sexual offenders because they experience higher stigmatization rates and difficulties towards social reintegration (Sreenivasan et al, 2022). Beyond this, race and sex also play a role in the stigmatization process from a blameworthiness, dangerousness, and social distance perspective.…”
Section: Introductionmentioning
confidence: 99%
“…A study in the UK identified 5 common themes (employment, housing, skills and experience, physical/psychological wellbeing, and addictions/antisocial behavior) in which stigmatization was made based on erroneous stereotypes that exacerbated the difficulties toward social reintegration (Phillips, 2020). Intersectionality aspects may also be considered in the case of homeless veterans who are also sexual offenders because they experience higher stigmatization rates and difficulties towards social reintegration (Sreenivasan et al, 2022). Beyond this, race and sex also play a role in the stigmatization process from a blameworthiness, dangerousness, and social distance perspective.…”
Section: Introductionmentioning
confidence: 99%